2022
DOI: 10.25130/tjas.22.3.15
|View full text |Cite
|
Sign up to set email alerts
|

The importance of crop rotation and some inducing factors in indicators of infection of wheat Galls nematode Anguina tritici

Abstract: The field experiment was carried out in the fields of a farmer in Kirkuk governorate / Hawija district N 43º36´17.73"E"05.56´ 35º16, and the study included the planting of the crop rotation crops (mung beans, sunflower and sesame and without planting) in the summer For the year 2020, and in the winter season, the wheat crop, Sham 6 variety, was planted in the experimental units planted with the crops of the agricultural rotation, as well as fallow land that was not planted with any previous crop. The wheat cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
2
0
0
Order By: Relevance
“…The analysis of variance table (1) shows that the parental genotypes differed significantly at the level of probability (1%) for all studied traits except for the number active tillers plant -1 , which differed significantly from the level of probability (5%), while the first-generation crosses (Table 2) differed significant in all the studied traits at the level of probability (1%) except for the characteristic of the number of spikelet's, spike -1 , which differed significantly at the level of probability (5%). This result agreed with [12], [13].…”
Section: Resultssupporting
confidence: 88%
“…The analysis of variance table (1) shows that the parental genotypes differed significantly at the level of probability (1%) for all studied traits except for the number active tillers plant -1 , which differed significantly from the level of probability (5%), while the first-generation crosses (Table 2) differed significant in all the studied traits at the level of probability (1%) except for the characteristic of the number of spikelet's, spike -1 , which differed significantly at the level of probability (5%). This result agreed with [12], [13].…”
Section: Resultssupporting
confidence: 88%
“…It is noted from the tables of the analysis of variance (1) that the parental genotypes differed significantly at the level of probability (1%) in all the studied traits except for the number of active tillers plant -1 differed significantly from the level of probability (5%), and from the table of the analysis of variance (2) It was found that the first-generation hybrids were significant in all the studied traits at the level of probability (1%) except for the number of spikelet's spike -1 differed significantly from the level of probability (5%), This is evidence of the genetically different parental genotypes, as well as the difference in crosses resulting from half-diallel crosses. This result agreed with [12,13].…”
Section: Resultssupporting
confidence: 87%